1020 MHz Single-Channel Proton Fast Magic Angle Spinning Solid-State NMR Spectroscopy - Pandey, Manoj Kumar (J Magn Reson, 2015)
This study reports a first successful demonstration of a single channel proton 3D and 2D high-throughput ultrafast magic angle spinning (MAS) solid-state NMR techniques in an ultra-high magnetic field (1020 MHz) NMR spectrometer comprised of HTS/LTS magnet. High spectral resolution is well demonstrated.